Congenital nystagmus cosegregating with a balanced 7;15 translocation. Issue 6 (June 1993) - Patton, M A; Jeffery, S; Lee, N; Hogg, C
Abstract : We report a family in which autosomal dominant congenital nystagmus cosegregates with a balanced 7;15 translocation. Ophthalmic investigation showed predominantly horizontal nystagmus with a small rotatory component and no significant loss of visual function. This finding suggests a possible localisation for autosomal dominant congenital nystagmus (McKusick 164100).